2015
DOI: 10.1007/s00405-014-3454-z
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge survey on 4,199 peritonsillar abscesses in the Veneto region: what is the risk of recurrence and complications without tonsillectomy?

Abstract: The Veneto region's database of hospital discharge records was queried for ICD-9 codes corresponding to: peritonsillar abscess (PTA), PTA incision and drainage, tonsillectomy, pharyngeal-retropharyngeal abscess, cervical phlegmon, cervical abscess, and mediastinitis recorded from 1997 to 2006. All these codes were considered to identify cases of PTA recurrence and severe infectious complications occurring in conservatively treated patients. Among 4,199 patients whose PTA was incised and drained on admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…The PTA group's age distribution in our study was similar to that reported in the literature. The distribution of gender in our study differs from previous studies which have demonstrated male predominance [17][18][19]. The age of the other subgroups (AT, CT) could not be analysed reliably, because they were formed based on the age range.…”
Section: Discussioncontrasting
confidence: 91%
“…The PTA group's age distribution in our study was similar to that reported in the literature. The distribution of gender in our study differs from previous studies which have demonstrated male predominance [17][18][19]. The age of the other subgroups (AT, CT) could not be analysed reliably, because they were formed based on the age range.…”
Section: Discussioncontrasting
confidence: 91%
“…We found 38 studies reporting a total of 113 patients with PTA-associated DM [ 67 104 ]. The median age was 52 years and there was a significant male preponderance (65%, 34/52, p = 0.04, Binomial probability test).…”
Section: Resultsmentioning
confidence: 99%
“…As recommended by The American College of Radiology–American Society of Neuroradiology–Society of Pediatric Radiology , we did not alter the scan length in the caudal direction to ensure reliable diagnosis of potentially life-threatening complications of cervical abscesses in the upper thorax, such as mediastinitis [5]. Although in our study cohort no patient was diagnosed with mediastinitis, since this is a relatively rare complication [29], we still consider it relevant not to shorten the scan range in the caudal direction in favor of patient dose reduction.…”
Section: Discussionmentioning
confidence: 99%